Method for producing fluoroolefin
By using a high-content α-alumina catalyst and controlling reaction conditions, the problems of low conversion rate of fluoroolefins and the decrease in conversion rate during long-term manufacturing in existing technologies have been solved, and a highly efficient method for manufacturing fluoroolefins has been realized.
Patent Information
- Application Number
- CN202480028105.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-26
- Filing Date
- 2024-04-01
- Publication Date
- 2025-11-25
AI Technical Summary
In existing technologies, when γ-alumina, θ-alumina, or α-alumina are used as catalysts, the conversion rate of fluoroolefins is low and decreases over long manufacturing periods.
The catalyst contained 65% or more of α-alumina, and the Lewis acid site content, determined by ammonia temperature-programmed desorption method, was 0.005–0.10 mmol/g. The fluorocarbons and the catalyst were controlled to contact in the gas phase in the presence of an inert gas at a contact temperature of 300–800 °C, and the water concentration was controlled to be below 500 ppm by mass.
It improves the conversion rate of fluoroolefins and inhibits the decrease in conversion rate during long-term manufacturing, maintaining high catalytic activity.
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This disclosure relates to a method for manufacturing fluoroolefins. Background Technology
[0002] In recent years, fluoroolefins, as compounds with low greenhouse effect potential, have been attracting attention.
[0003] For example, Patent Document 1 discloses a method for manufacturing fluoroolefins, which includes a defluorination step of contacting a fluorocarbon compound with a metal catalyst to perform defluorination. The defluorination step is carried out in the gas phase in the presence of water, with a water concentration of 500 ppm relative to the fluorocarbon compound, and γ-alumina is used as the catalyst. Furthermore, Non-Patent Document 1 discloses a method for obtaining trifluoroethylene using α-alumina, γ-alumina, θ-alumina, etc., in the defluorination reaction of 1,1,1,2-tetrafluoroethane.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-196347
[0007] Non-patent literature
[0008] Non-patent literature 1: Catalysis Letters, 2015, Vol. 145, pp. 654-661 Summary of the Invention
[0009] The technical problem that the invention aims to solve
[0010] However, when using γ-alumina as a catalyst as described in Patent Document 1, there is a tendency for the conversion rate to decrease over long manufacturing periods. Furthermore, when using γ-alumina, θ-alumina, or a combination thereof as catalysts as described in Non-Patent Document 1, although the initial conversion rate is high, it decreases over long manufacturing periods. Moreover, when using α-alumina as a catalyst, the conversion rate is very low, at 1.2%.
[0011] The technical problem of one embodiment of the present invention is to provide a method for manufacturing fluoroolefins with a higher conversion rate than before and with suppression of the decrease in conversion rate during long-term manufacturing.
[0012] Technical solutions adopted to solve technical problems
[0013] This disclosure includes the following technical content.
[0014] <1> A method for manufacturing fluoroolefins includes a step of contacting a fluorocarbon compound of formula (1) with a catalyst to manufacture a fluoroolefin of formula (2).
[0015] The catalyst described above contains more than 65% by mass of α-alumina, and the amount of Lewis acid sites, as determined by ammonia temperature-programmed desorption, is 0.005–0.10 mmol / g.
[0016] CX 1 X 2 F-CX 3 X 4 H …(1)
[0017] CX 1 X 2 =CX 3 X 4 …(2)
[0018] In equations (1) and (2), X 1 X 2 X 3 and X 4 Each can be represented independently as a hydrogen atom or a fluorine atom, where X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
[0019] <2> like <1> In the method for manufacturing the fluoroolefin, the amount of the Lewis acid site is 0.005 to 0.05 mmol / g.
[0020] <2> like <1> or <2> In the method for manufacturing the fluoroolefin, the amount of the Lewis acid site is 0.008 to 0.05 mmol / g.
[0021] <4> like <1> ~ <3> The method for producing fluoroolefins according to any one of the above methods, wherein the amount of the fluorocarbon compound supplied to the catalyst is 350 kg / hr / m 3 above.
[0022] <5> like <1> ~ <4> The method for manufacturing fluoroolefins according to any one of the following methods, wherein the fluorocarbon compound is at least one selected from 1,1,1-trifluoroethane, 1,1,2-trifluoroethane, 1,1,2,2-tetrafluoroethane and 1,1,1,2-tetrafluoroethane.
[0023] <6> like <1> ~ <5> The method for manufacturing a fluoroolefin according to any one of the following methods, wherein the fluoroolefin is at least one selected from 1,2-difluoroethylene, 1,1-difluoroethylene and trifluoroethylene.
[0024] <7> like <1> ~ <6> The method for manufacturing a fluoroolefin according to any one of the following methods, wherein the fluorocarbon compound is 1,1,1,2-tetrafluoroethane and the fluoroolefin is trifluoroethylene.
[0025] <8> like <1> ~ <7> The method for producing fluoroolefins according to any one of the above methods, wherein the fluorocarbon compound is contacted with the catalyst at a temperature of 300 to 800°C.
[0026] <9> like <1> ~ <8> The method for producing fluoroolefins according to any one of the following, wherein,
[0027] The fluorocarbon compound and the catalyst are brought into contact in the presence of an inert gas.
[0028] The aforementioned inert gas is selected from at least one of nitrogen, helium, argon, octafluorocyclobutane, and carbon dioxide.
[0029] <10> like <1> ~ <9> The method for producing fluoroolefins according to any one of the above methods further includes a step of drying the catalyst before contacting the fluorocarbon compound with the catalyst.
[0030] <11> like <1> ~ <10> The method for producing fluoroolefins according to any one of the following, wherein,
[0031] The fluorocarbon compound and the catalyst are brought into contact in the gas phase in the presence of water.
[0032] The concentration of the water is less than 500 ppm by mass relative to the total amount of the feed gas containing the fluorocarbons.
[0033] <12> A method for manufacturing fluoroolefins includes a step of contacting a fluorocarbon compound of formula (1) with a catalyst to manufacture a fluoroolefin of formula (2).
[0034] The conversion rate of the above-mentioned fluorocarbon compound after contacting the above-mentioned catalyst for 10 hours is 7-13.0%, and the conversion rate after 50 hours relative to the conversion rate after 10 hours, i.e., the conversion rate retention rate, is above 69%.
[0035] CX 1 X 2 F-CX 3 X 4 H …(1)
[0036] CX 1 X 2 =CX 3 X 4 …(2)
[0037] In equations (1) and (2), X 1 X 2 X 3 and X 4 Each can be represented independently as a hydrogen atom or a fluorine atom, where X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
[0038] Invention Effects
[0039] According to this disclosure, a method for manufacturing fluoroolefins with a higher conversion rate than before and with suppressed reduction in conversion rate during long-term manufacturing can be provided. Attached Figure Description
[0040] Figure 1 The diffraction pattern is obtained by XRD analysis of the catalyst in Example 6. Detailed Implementation
[0041] In this disclosure, the numerical range represented by “~” refers to the range that includes the minimum and maximum values recorded before and after “~”, respectively.
[0042] In this disclosure, the upper or lower limit of a numerical range recorded in a certain numerical range can be replaced with the upper or lower limit of another numerical range recorded in a different level. Furthermore, the upper or lower limit of a numerical range recorded in this disclosure can also be replaced with the values shown in the embodiments.
[0043] In this disclosure, a combination of two or more preferred forms is a more preferred form.
[0044] In this disclosure, where there are multiple substances equivalent to each component, unless otherwise expressly specified, the amount of each component refers to the total amount of the multiple substances.
[0045] In this disclosure, "long-term manufacturing" refers to manufacturing by contacting the fluorocarbon compound with the catalyst for 50 hours, or manufacturing for more than 50 hours.
[0046] [Manufacturing methods for fluoroolefins]
[0047] The method for manufacturing fluoroolefins according to the first embodiment of this disclosure includes a step of contacting a fluorocarbon compound represented by formula (1) with a catalyst to manufacture a fluoroolefin represented by formula (2), wherein the catalyst contains 65% by mass or more of α-alumina and the amount of Lewis acid sites determined by ammonia temperature-programmed desorption method is 0.005 to 0.10 mmol / g.
[0048] The second embodiment of the present disclosure of the method for manufacturing fluoroolefins includes a step of contacting a fluorocarbon compound of formula (1) with a catalyst to manufacture a fluoroolefin of formula (2), wherein the conversion rate after 10 hours of contacting the fluorocarbon compound with the catalyst is 7.0 to 13.0%, and the conversion rate after 50 hours is the ratio of the conversion rate after 10 hours to the conversion rate after 10 hours, i.e., the conversion rate maintenance rate is 69% or more.
[0049] CX 1 X 2 F-CX 3 X 4 H …(1)
[0050] CX 1 X 2 =CX 3 X 4 …(2)
[0051] In equations (1) and (2), X 1 X 2 X 3 and X 4 Each can be represented independently as a hydrogen atom or a fluorine atom, where X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
[0052] The method for manufacturing fluoroolefins according to the first embodiment and the method for manufacturing fluoroolefins according to the second embodiment are also collectively referred to as the method for manufacturing fluoroolefins disclosed herein.
[0053] According to the method for manufacturing fluoroolefins disclosed herein, the conversion rate is higher than before, and the decrease in conversion rate during long-term manufacturing is suppressed. The reason for this is not yet clear, but it is speculated as follows.
[0054] In the reaction of obtaining the fluoroolefin shown in formula (2) from the fluorocarbon compound shown in formula (1), hydrogen fluoride is produced. The produced hydrogen fluoride reacts with the fluoroolefin shown in formula (2) to return to the fluorocarbon compound shown in formula (1). Therefore, the conversion rate of the fluorocarbon compound shown in formula (1) has been very low in the past.
[0055] In this regard, the inventors discovered that when using a catalyst containing 65% by mass or more α-alumina and having a Lewis acid site concentration of 0.005 mmol / g or more as determined by ammonia temperature-programmed desorption, the conversion rate is improved. This is believed to be due to the presence of an effective amount of active sites in the catalyst that activate the CF bond, thus exhibiting defluorination reactivity.
[0056] It was also found that when using a catalyst containing more than 65% by mass of α-alumina and with a Lewis acid site concentration of more than 0.10 mmol / g as determined by ammonia temperature-programmed desorption, the decline in catalyst activity during long-term manufacturing was suppressed. This is attributed to the moderate suppression of fluorination of the catalyst by the hydrofluoric acid produced in the reaction. It is also believed that this is due to the moderate suppression of coking phenomena caused by the accumulation of carbon from feedstock decomposition on the catalyst.
[0057] On the other hand, Patent Document 1 describes a method for manufacturing fluoroolefins using γ-alumina. However, since the crystal structure of γ-alumina changes significantly at high temperatures, the conversion rate tends to decrease over long periods of manufacturing when using γ-alumina as a catalyst.
[0058] Furthermore, Non-Patent Literature 1 describes a method for producing trifluoroethylene using Al₂O₃-1200 containing 100% by mass α-alumina. According to the document, in ammonia-programmed temperature desorption (NH₃-TPD) or pyridine adsorption infrared spectroscopy (Py-IR) analysis, Al₂O₃-1200 does not possess Brønsted acid sites, but the amount of Lewis acid sites is 0.004 mmol / g. According to the document, the conversion rate is approximately 1.2% when using Al₂O₃-1200. It is speculated that the low conversion rate is due to the low amount of Lewis acid sites in Al₂O₃-1200, resulting in fewer active sites on the catalyst.
[0059] Non-Patent Document 1 also describes a method for producing trifluoroethylene using Al₂O₃-1150 containing 64.3% by mass of α-alumina and having an acid site concentration of 0.006 mmol / g. According to the document, the conversion rate is approximately 1.2% when using Al₂O₃-1150.
[0060] In addition, Non-Patent Literature 1 calculates the amount of fluorocarbons supplied to the catalyst, resulting in 307 kg / h / m³. 3 Setting a low raw material supply is a condition for achieving a high conversion rate. However, if the raw material supply is low, industrial productivity decreases, thus requiring an increase in the raw material supply. In Non-Patent Literature 1, if the raw material supply is increased, the conversion rate will be lower than the aforementioned value.
[0061] Non-Patent Literature 1 also describes a method for producing trifluoroethylene using an alumina catalyst with an acid site concentration of 0.065–0.362 mmol / g. These alumina catalysts are composed of γ-alumina, θ-alumina, etc., but do not contain α-alumina. When using these alumina catalysts, the initial conversion rate is high, but it decreases significantly after 15 hours. It is speculated that this is because, as mentioned above, γ-alumina, θ-alumina, etc., whose crystal structure is easily altered at high temperatures, are used.
[0062] Furthermore, in Non-Patent Literature 1, manufacturing was carried out under high conversion conditions, with an initial conversion rate of approximately 28% or higher and a conversion rate of 20% or higher after 10 hours. Under these conditions, the conversion rate significantly decreased after 15 hours. The reason given is that if the initial conversion rate is too high, the amount of hydrogen fluoride produced increases, thus intensifying fluorination, one of the causes of catalyst deactivation. If fluorination of the catalyst intensifies, the catalyst is prone to coking, ultimately leading to catalyst deactivation. In Non-Patent Literature 1, when the manufacturing time is further extended to 50 hours, it is expected that catalyst deactivation will intensify, and the conversion rate will further decrease.
[0063] Therefore, as in the method for manufacturing fluoroolefins according to the second embodiment, by suppressing the conversion rate of the fluorocarbon compound to 7-13% after 10 hours of contact with the catalyst, the conversion rate is maintained at 69% or more after 50 hours. As a method to effectively suppress the conversion rate to 7-13% after 10 hours, the catalyst of the first embodiment is preferably used.
[0064] (The fluorocarbon compound shown in formula (1))
[0065] In the method for manufacturing fluoroolefins disclosed herein, a fluorocarbon compound represented by the following formula (1) can be used as a raw material.
[0066] CX 1 X 2 F-CX 3 X 4 H …(1)
[0067] In equation (1), X 1 X 2 X 3 and X 4 Each can be represented independently as a hydrogen atom or a fluorine atom, where X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
[0068] The following compounds can be cited as examples of fluorocarbon compounds represented by formula (1).
[0069] CHF2CH3: 1,1-Difluoroethane (HFC-152a)
[0070] CH2FCH2F: 1,2-Difluoroethane (HFC-152)
[0071] CF3CH3: 1,1,1-Trifluoroethane (HFC-143a)
[0072] CHF2CH2F: 1,1,2-Trifluoroethane (HFC-143)
[0073] CF3CH2F: 1,1,1,2-Tetrafluoroethane (HFC-134a)
[0074] CHF2CHF2: 1,1,2,2-Tetrafluoroethane (HFC-134)
[0075] CF3CHF2: 1,1,1,2,2-Pentafluoroethane (HFC-125)
[0076] From the viewpoint of minimizing side reactions and suppressing the formation of byproducts, the fluorocarbon compound represented by formula (1) is preferably selected from at least one of HFC-143a, HFC-143, HFC-134a, and HFC-134. Furthermore, since one fluoroolefin can be obtained with a high selectivity, the fluorocarbon compound represented by formula (1) is preferably HFC-134a.
[0077] (The fluoroolefin shown in formula (2))
[0078] In the method for manufacturing fluoroolefins disclosed herein, fluoroolefins as shown in the following formula (2) are obtained as reaction products.
[0079] CX 1 X 2 =CX 3 X 4 …(2)
[0080] In equation (2), X 1 X 2 X 3 and X 4 Each can be represented independently as a hydrogen atom or a fluorine atom, where X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
[0081] The following compounds can be cited as examples of fluoroolefins represented by formula (2).
[0082] CHF=CH2: Vinyl fluoride
[0083] CF2=CH2: 1,1-Difluoroethylene (HFO-1132a)
[0084] CHF=CHF: 1,2-Difluoroethylene (HFO-1132(E), HFO-1132(Z))
[0085] CHF=CF2: Trifluoroethylene (HFO-1123)
[0086] CF2=CF2: Tetrafluoroethylene
[0087] From the viewpoint of its usefulness as a refrigerant composition, the fluoroolefin represented by formula (2) is preferably at least one selected from HFO-1132, HFO-1132a and HFO-1123.
[0088] In particular, in the method for manufacturing fluoroolefins disclosed herein, from the viewpoint of more selective reaction, the fluorocarbon compound is preferably HFC-134a and the fluoroolefin is preferably HFO-1123.
[0089] In addition, olefins other than the fluoroolefins of formula (2) can also be generated together with the fluoroolefins shown in formula (2). As olefins other than the fluoroolefins of formula (2), ethylene can be included.
[0090] (catalyst)
[0091] In the method for manufacturing fluoroolefins disclosed herein, a fluorocarbon compound represented by formula (1) is contacted with a catalyst.
[0092] The catalyst in contact with fluorocarbons contains more than 65% by mass of α-alumina and has a Lewis acid site content of 0.005–0.10 mmol / g as determined by ammonia temperature-programmed desorption (NH3-TPD).
[0093] Alumina is a dehydration product of aluminum hydroxide, and its properties vary depending on the degree of dehydration and crystallinity. Based on crystal structure, alumina exists in various types, including γ-alumina, θ-alumina, and α-alumina. γ-alumina and θ-alumina are known as active alumina, with higher formation free energies than α-alumina and are thermodynamically unstable. The highly crystalline, high-temperature stable phase is α-alumina, which has a smaller specific surface area but is thermally stable and has high thermal conductivity. The catalyst used in the method for producing fluoroolefins disclosed herein contains α-alumina. Compared to other alumina structures, α-alumina has a higher barrier for the conversion of Al-O to Al-F in the presence of hydrogen fluoride; by using a catalyst containing α-alumina, the formation of AlF3 can be suppressed. It is believed that the formation of AlF3 leads to catalyst deactivation and reduced selectivity.
[0094] The presence of α-alumina in a catalyst can be confirmed by X-ray diffraction, or in other words, by the diffraction pattern obtained from an XRD (X-ray Diffractometer). Commercially available equipment can be used for XRD, such as the "SmartLab" instrument manufactured by Rigaku Corporation. In the diffraction pattern, the presence of peaks at d=26.62, 35.21, 37.85, 43.43, 52.65, and 57.61 Å indicates the presence of α-alumina. Furthermore, this analysis is performed on the catalyst just before contact with the fluorocarbon compound, or on a catalyst that reverts to the same state as before contact with the fluorocarbon compound.
[0095] In addition, by including more than 65% by mass of α-alumina in the catalyst, the catalyst exhibits high durability and can suppress the decrease in conversion rate even during long-term manufacturing.
[0096] The presence of α-alumina at a concentration of 65% or more by mass in the catalyst can be confirmed by Rietveld analysis of the crystal structure obtained from XRD. Specifically, the mass proportion of each crystal structure is calculated by comparing the peaks obtained from XRD measurements of the catalyst with known peak models derived from each alumina structure and performing Rietveld analysis.
[0097] The catalyst contains 65% by mass or more of α-alumina, preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, and may also contain 100% by mass.
[0098] Catalysts can also contain compounds other than α-alumina. Examples of compounds other than α-alumina include alumina with a different crystal structure than α-alumina, and oxides other than alumina. Examples of alumina with a different crystal structure than α-alumina include β-alumina, γ-alumina, θ-alumina, η-alumina, boehmite, and gibbsite. Examples of oxides other than alumina include chromium oxide, copper oxide, iron oxide, nickel oxide, magnesium oxide, zinc oxide, and zirconium oxide.
[0099] In addition, the catalyst may also contain compounds other than α-alumina, such as aluminum fluoride or aluminum fluoride obtained by fluorinating α-alumina.
[0100] Alpha-alumina not only acts as a catalyst, but also as a support. Furthermore, alpha-alumina can also be supported on supports other than alpha-alumina.
[0101] Examples of carriers include carbon, β-alumina, γ-alumina, zirconium oxide, silicon oxide, and titanium oxide.
[0102] The amount of Lewis acid sites of the catalyst, as determined by the ammonia temperature-programmed desorption method, is 0.005–0.10 mmol / g, preferably 0.005–0.05 mmol / g, and more preferably 0.008–0.05 mmol / g from the viewpoint of further suppressing the decrease in conversion rate after 100 hours.
[0103] The catalyst can be a dried catalyst, an activated catalyst, a catalyst that has undergone both treatments, or a catalyst that has not undergone either treatment. The catalyst state in this invention refers to the state of the catalyst at the start of the reaction (just before the reaction begins). Under various treatments, the treated catalyst becomes the target for Lewis acid site determination. Furthermore, if the amount of acid sites remains essentially unchanged even after various treatments, the Lewis acid sites can be determined from the catalyst before treatment.
[0104] The ammonia-programmed temperature desorption method involves adsorbing ammonia (NH3) onto the sample, then continuously heating at a constant rate to determine the amount of ammonia desorbed and the desorption temperature. The amount of acid in the sample can be determined based on the amount of desorbed NH3. Furthermore, since NH3 adsorbed on weak acid sites desorbs at low temperatures and NH3 adsorbed on strong acid sites desorbs at high temperatures, the acid strength of the sample can also be determined.
[0105] Therefore, in this disclosure, the peak intensity of the amount of ammonia desorbed at temperatures below 200°C is used as the amount of Brønsted acid sites, and the peak intensity of the amount of ammonia desorbed at temperatures above 200°C is used as the amount of Lewis acid sites, in order to distinguish between Brønsted acid sites and Lewis acid sites.
[0106] In addition, Lewis acid sites are acid sites that accept electron pairs from the target molecule, while Brønsted acid sites are acid sites that donate protons to the target molecule.
[0107] The determination of ammonia by temperature-programmed desorption (NH3-TPD) was performed using a catalyst analyzer (e.g., MicrotracBEL, “BELCAT II”). In the determination, the temperature was increased to 810°C at a rate of 10°C / min and held for 10 minutes. Helium was used as the carrier gas at a flow rate of 50 mL / min (sccm).
[0108] Before the determination, the catalyst can be pretreated. Examples of pretreatment include steps 1 through 6 described below. Then, the temperature is increased as described above to desorb NH3 from the catalyst, the desorption temperature and amount are measured, and the amount of Lewis acid sites is analyzed. Additionally, the NH3 used in step 5 below has been diluted with He, and the concentration of NH3 is 5.05% by volume. Therefore, the gas composition in step 5 below is: He: 90 + 10 × 0.9495 = 99.495 sccm, NH3: 10 × 0.0505 = 0.505 sccm.
[0109] [Table 1]
[0110]
[0111] The form of the catalyst is not particularly limited; it can be powder, granules, or spheres.
[0112] From the viewpoints of excellent fillability when filling the reactor, excellent flowability of reaction gases, and operability during use for about 10 hours, α-alumina is preferably a shaped body such as spherical or granular.
[0113] A molded body is a body that is different from a powder, such as a body obtained by compressing powder into a mold.
[0114] (Reaction conditions)
[0115] In the method for manufacturing fluoroolefins disclosed herein, the feed gas may contain only the fluorocarbon compound shown in Formula (1), or may contain components other than the fluorocarbon compound shown in Formula (1). The feed gas may consist only of the fluorocarbon compound shown in Formula (1), or may contain isomers, disproportionation products, impurities, etc., obtained during the manufacturing of the fluorocarbon compound shown in Formula (1). From the viewpoint of suppressing side reactions and catalyst deactivation, the feed gas preferably contains inert gases such as nitrogen, argon, helium, carbon dioxide, and octafluorocyclobutane in addition to the fluorocarbon compound shown in Formula (1). The inert gases can dilute the target product and the byproduct hydrogen fluoride. The content of the fluorocarbon compound shown in Formula (1) relative to the total amount of the feed gas is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 75 mol% or more, and particularly preferably 80 mol% or more.
[0116] The method for producing fluoroolefins disclosed herein can be carried out in the gas phase or in the liquid phase. The fluorocarbon compound represented by formula (1) is a gas at room temperature, therefore it is preferable to contact the fluorocarbon compound with the catalyst in the gas phase.
[0117] As a reactor that brings fluorocarbons into contact with a catalyst, any reactor capable of withstanding the temperature and pressure described later is acceptable, and its shape and structure are not particularly limited. Examples of reactors include, for instance, a cylindrical vertical reactor. Examples of reactor materials include glass, stainless steel, iron, nickel, and alloys primarily composed of iron or nickel. The reactor may also be equipped with heating elements such as electric heaters to heat the interior.
[0118] The catalyst can be contained in any of the following forms: fixed bed, fluidized bed, or moving bed. In the case of a fixed bed, it can be either a horizontal fixed bed or a vertical fixed bed.
[0119] In addition, the reaction can be either flow-through or batch reaction.
[0120] In fixed-bed reactors, various shaped supports carrying the catalyst are filled to reduce pressure loss of the reaction fluid. A moving-bed reactor, similar to a fixed-bed reactor, fills the reactor with catalyst and allows it to be discharged from the bottom by gravity for recycling. In fluidized-bed reactors, catalyst particles are suspended in the reaction fluid and move within the reactor to allow the catalyst bed to exhibit fluid-like properties. A wide range of catalyst shapes are possible, but fixed-bed reactors are preferred from the viewpoint of suppressing catalyst attrition. Fixed-bed reactors include tubular reactors and trough reactors; tubular reactors are preferred for ease of temperature control. Furthermore, multi-tube heat exchange reactors can be used, where multiple small-diameter reaction tubes are arranged in parallel and the heat medium circulates on the outside. When multiple reactors are connected in series, multiple catalyst beds are provided. At least one catalyst bed is sufficient, but two or more are also possible.
[0121] From the viewpoint of improving conversion rate, the method for producing fluoroolefins disclosed herein is preferably carried out in a flow manner using a fixed-bed reactor (especially a vertical fixed-bed reactor).
[0122] From the perspective of improving industrial productivity, the amount of fluorocarbons supplied to the catalyst (raw material supply) is preferably 350 kg / hr / m³. 3 The above is preferred, specifically 375 kg / hr / m 3 The above is further optimized to 400kg / hr / m 3 That's all. Furthermore, from the viewpoint of maintaining a constant or higher conversion rate, the feedstock supply is preferably 3000 kg / hr / m³. 3 Below, 2500 kg / hr / m is preferred. 3 The following is a further preferred option: 2000 kg / hr / m 3 the following.
[0123] In addition, the raw material supply refers to the amount of raw materials supplied per unit time to each 1m 3 The amount (kg / hr) of fluorocarbon (feed) supplied to the catalyst is preferably within the above range.
[0124] In the method for producing fluoroolefins disclosed herein, it is preferable to contact the fluorocarbon compound with the catalyst at a temperature of 300–800°C, more preferably at a temperature of 400–700°C, and even more preferably at a temperature of 400–600°C. If the contact temperature is above 300°C, the conversion rate of the fluoroolefin is increased. On the other hand, if the contact temperature is below 800°C, the decomposition of the fluoroolefin can be suppressed.
[0125] If the contact temperature is above 300°C, the reaction proceeds moderately. On the other hand, if the contact temperature is below 800°C, the decrease in selectivity caused by the breaking of carbon-carbon bonds in the raw materials and the disproportionation reaction of the product (unsaturated compound) can be suppressed.
[0126] The defluorination reaction is typically endothermic; therefore, maintaining an appropriate reaction temperature can suppress any decrease in conversion rate. Increasing the reaction temperature within the catalyst bed increases the conversion rate of the reactants. Therefore, to maintain a high conversion rate, it is preferable to keep the reaction temperature within the catalyst bed at the desired level. To maintain the desired reaction temperature within the catalyst bed, methods such as externally heating the catalyst bed using a heat transfer medium can be employed. Catalysts typically degrade over time as the reaction proceeds. When catalyst degradation leads to a decrease in reactant conversion rate, heating the catalyst bed with a heat transfer medium or similar means can appropriately maintain or increase the reaction temperature, thereby suppressing the decrease in conversion rate. When maintaining or increasing the temperature of the catalyst bed, to suppress rapid catalyst degradation, it is preferable to keep the temperature increase below 50°C.
[0127] The reaction zone begins at the inlet of the feed gas at the start of the reaction. If the catalyst at the feed gas inlet deteriorates over time as the reaction proceeds, the reaction zone shifts downstream in the direction of gas flow. The low-temperature generated gas in the reaction zone flows into the vicinity of the downstream side of the reaction zone, which is typically the lowest temperature portion of the catalyst layer. In this disclosure, the temperature of this lowest temperature region of the catalyst layer is denoted as the "lowest temperature of the catalyst layer." The temperature further downstream than this vicinity typically increases from the lowest temperature of the catalyst layer with distance from the reaction zone.
[0128] In the method for producing fluoroolefins disclosed herein, the feed gas containing fluorocarbons can also be directly supplied to the reactor at room temperature. However, it is preferable that the feed gas be appropriately heated (preheated) before being supplied to the reactor. When preheating is performed, it is preferable to heat the feed gas to a temperature of 80–600°C before supplying it to the reactor. If preheated to above 80°C, the internal temperature of the reactor is less likely to decrease, making it easier to achieve the set conversion rate. Furthermore, if preheated to below 600°C, the internal temperature of the reactor is less likely to rise, undesirable reactions are inhibited, and selectivity is improved.
[0129] The defluorination reaction in this disclosure is a molecular increase reaction, so increasing the pressure is not conducive to the forward reaction.
[0130] There is no particular limitation on the pressure at which the fluorocarbon compound comes into contact with the catalyst. From the viewpoint of improving the conversion rate, it is preferably -0.05 to 2 MPa, more preferably -0.01 to 1 MPa, and even more preferably atmospheric pressure to 0.5 MPa.
[0131] In this disclosure, pressure refers to gauge pressure.
[0132] The contact time (in seconds) between the fluorocarbon compound and the catalyst is preferably 0.5 to 100.0 seconds, more preferably 1.0 to 50.0 seconds, and even more preferably 2.0 to 20.0 seconds.
[0133] The contact time (in seconds) mentioned above is calculated using the following formula.
[0134] Contact time (seconds) = [Length of catalyst packed in the reactor (cm)] / [Linear velocity (cm / second)]
[0135] Linear velocity refers to the rate at which fluorocarbons pass through a catalyst per unit time.
[0136] Furthermore, the contact time (g·s / mL) between the fluorocarbon compound and the catalyst is preferably 1–200 g·s / mL, more preferably 5–175 g·s / mL, even more preferably 7–150 g·s / mL, and particularly preferably 10–125 g·s / mL. If the contact time (g·s / mL) is 1 g·s / mL or more, the conversion rate is improved. If the contact time (g·s / mL) is 200 g·s / mL or less, equipment costs can be reduced.
[0137] The contact time (g·second / mL) mentioned above is calculated using the following formula.
[0138] Contact time (g·second / mL) = [catalyst loading amount (g)] / [fluorocarbon flow rate (mL / second)]
[0139] From the viewpoint of further suppressing the decrease in conversion rate, it is preferable to contact the fluorocarbon compound with the catalyst in the presence of an inert gas. The inert gas is preferably at least one selected from nitrogen, helium, argon, octafluorocyclobutane, and carbon dioxide. Nitrogen is particularly preferred. Furthermore, in this disclosure, an inert gas refers to a gas that is inert to the reaction with the raw materials.
[0140] The molar ratio of fluorocarbons in the gas phase to the inert gas is preferably 0.1 to 30, more preferably 0.5 to 25.
[0141] From the viewpoint of further suppressing the decrease in conversion rate, it is preferable to contact the fluorocarbon compound with the catalyst in the gas phase in the presence of water, and the concentration of water relative to the total amount of feed gas containing the fluorocarbon compound is less than 500 ppm by mass.
[0142] If the defluorination reaction is carried out in the gas phase in the presence of water, the water will adsorb onto Lewis acid sites on the catalyst surface. It is hypothesized that by keeping the water concentration below 500 ppm by mass relative to the total amount of the feed gas containing fluorocarbons, the destruction of Lewis acid sites on the catalyst surface and the formation of structures similar to Brønsted acid sites can be suppressed, thereby inhibiting the decrease in catalyst activity. It is hypothesized that this leads to improved conversion and the ability to obtain the target product with high selectivity. From the viewpoint of further improving conversion and obtaining the target compound with higher selectivity, the water concentration is preferably below 300 ppm by mass, more preferably below 100 ppm by mass, even more preferably below 50 ppm by mass, and particularly preferably below 10 ppm by mass. Lower water concentrations are better, but considering the cost of dehydration treatment of fluorocarbons and inert gases, and the difficulty of process management, a concentration of 0.5 ppm by mass or higher is preferred, more preferably above 1 ppm by mass.
[0143] As a general method for determining the concentration of water, one example is the use of a commercially available Karl Fischer moisture analyzer.
[0144] The water concentration mentioned above refers to the water content in the feed gas when the fluorocarbon compound comes into contact with the catalyst. Alternatively, the water concentration can also be replaced by the water content in the feed gas before it flows into the reactor.
[0145] The method for producing fluoroolefins disclosed herein preferably further includes a step of drying the catalyst before contacting the fluorocarbon compound with the catalyst. By drying the catalyst, water contained in the catalyst can be removed, thereby increasing its reactivity with the fluorocarbon compound and improving the conversion rate.
[0146] There is no particular limitation on the method of drying the catalyst; it can be dried before or after the catalyst is filled into the reactor. Drying after filling the reactor allows for simultaneous preheating of the reactor, which is therefore preferable. Specifically, it is preferable to fill the reactor with the catalyst while simultaneously heating the reactor with an inert gas to dry the catalyst.
[0147] In the method for producing fluoroolefins disclosed herein, hydrogen fluoride is generated as a byproduct. Hydrogen fluoride has the function of fluorinating oxides contained in the catalyst and enhancing acid properties. Therefore, it is preferable to reduce the concentration of hydrogen fluoride. Reducing the concentration of hydrogen fluoride maintains selectivity, suppresses catalyst deactivation, and inhibits the decrease in reaction activity due to a decrease in the specific surface area of the catalyst.
[0148] One method to reduce the concentration of hydrogen fluoride is to use an inert gas for dilution.
[0149] Since the use of inert gases increases the energy load of the post-reaction purification process, it is preferable to appropriately control the use of inert gases.
[0150] The concentration of hydrogen fluoride in the reaction is preferably 15 mol% or less. From the viewpoint of extending catalyst lifetime, the concentration of hydrogen fluoride is more preferably 13 mol% or less, further preferably 10 mol% or less, particularly preferably 8 mol% or less, and most preferably 7 mol% or less. Furthermore, from the viewpoint of productivity and energy load of the purification process, the concentration of hydrogen fluoride is preferably 0.5 mol% or more, more preferably 0.8 mol% or more, further preferably 1.0 mol% or more, particularly preferably 1.3 mol% or more, and most preferably 1.5 mol% or more.
[0151] The method for producing fluoroolefins disclosed herein is preferably carried out in the presence of an oxidant. From the viewpoint of high conversion and the ability to obtain the target compound with high selectivity, oxygen, chlorine, bromine, or iodine are preferred. Oxygen is more preferred as the oxidant. In this disclosure, the concentration of the oxidant is preferably 0.01 to 21 mol% relative to the feed gas. From the viewpoint of further improving the conversion and obtaining the target compound with even higher selectivity, the concentration of the oxidant is more preferably 1 to 20 mol% relative to the feed compound, more preferably 5 to 18 mol%, and particularly preferably 7.5 to 16 mol%.
[0152] In this disclosure, conversion rate represents the ratio (mol%) of the total molar amount of compounds other than feedstock compounds contained in the gas exiting the reactor outlet to the molar amount of feedstock compounds supplied to the reactor.
[0153] Generally, from a productivity standpoint, a higher conversion rate is better. However, in the defluorination reaction of this disclosure, it is preferable to appropriately control the conversion rate. It is believed that if the conversion rate is controlled, the concentration of hydrogen fluoride generated in the gas phase will decrease, which can suppress catalyst deactivation caused by hydrogen fluoride. Diluting the gas phase with an inert gas can also be considered, but using an inert gas would increase the energy load of the post-reaction purification process; therefore, it is preferable not to use excessive amounts of inert gas. From the viewpoint of extending catalyst lifetime, it is preferable to control the concentration of hydrogen fluoride in the reaction to below 15 mol%.
[0154] From the above perspective, it is preferable to select operating conditions in which the conversion rate of fluorocarbons after contacting the catalyst for 10 hours is 7 to 13%, and more preferably, operating conditions in which the conversion rate after 10 hours is 7.5 to 12.5%.
[0155] Preferably, the operating conditions are those with a conversion rate of 4.0% or higher after the fluorocarbon compound has been in contact with the catalyst for 50 hours; more preferably, the operating conditions are those with a conversion rate of 4.5% or higher; even more preferably, the operating conditions are those with a conversion rate of 5.0% or higher; and most preferably, the operating conditions are those with a conversion rate of 5.5% or higher.
[0156] Preferably, the operating conditions are those with a conversion rate of 1.0% or higher after the fluorocarbon compound has been in contact with the catalyst for 100 hours; more preferably, the operating conditions are those with a conversion rate of 2.0% or higher; even more preferably, the operating conditions are those with a conversion rate of 3.0% or higher; and most preferably, the operating conditions are those with a conversion rate of 4.0% or higher.
[0157] The conversion rate retention rate, i.e., the ratio of the conversion rate after 50 hours to the conversion rate after 10 hours, is preferably 69% or higher. Furthermore, the conversion rate retention rate after 100 hours of contacting the fluorocarbon compound with the catalyst is preferably 30% or higher, more preferably 40% or higher, and even more preferably 50% or higher.
[0158] In particular, in the method for producing fluoroolefins disclosed herein, by using HFC-134a as the fluorocarbon compound, the conversion rate does not become too high after 10 hours, and catalyst deactivation can be suppressed.
[0159] Furthermore, as a catalyst, by using a catalyst containing more than 65% by mass of α-alumina and having an amount of Lewis acid sites of 0.005 to 0.10 mmol / g as determined by ammonia temperature-programmed desorption, the conversion rate does not become excessively high after 10 hours, and catalyst deactivation can be suppressed.
[0160] In this disclosure, the selectivity rate represents the ratio (mol%) of the molar amount of the target product contained in the reactor outlet gas to the total molar amount of compounds other than the feedstock compounds contained in the reactor outlet gas.
[0161] Selectivity is preferably 100% because no post-reaction purification step is required, but side reactions may occur within the reaction temperature range necessary to obtain the desired conversion. Higher selectivity is better because it reduces waste, decreases the energy load of post-reaction purification steps, and extends catalyst lifetime.
[0162] The selectivity of the fluorocarbon compound after contacting the catalyst for 50 hours is preferably above 90%, more preferably above 93%, and even more preferably above 95%.
[0163] In particular, in the method for manufacturing fluoroolefins disclosed herein, HFO-1123 can be obtained with high selectivity by using HFC-134a as the fluorocarbon compound.
[0164] Examples of compounds other than the feedstock and target products contained in the reactor outlet gas include hydrogen fluoride, carbon monoxide, carbon dioxide, and water. For example, when using HFC-134a as a fluorocarbon compound (i.e., a feedstock compound), other examples of compounds include HFC-134, 1,1-difluoroethylene (VdF), and E / Z-1,2-difluoroethylene (HFO-1132(E) / (Z)).
[0165] Example
[0166] The present disclosure is illustrated in more detail below by way of examples, but the present disclosure is not limited to the following examples without departing from its technical concept.
[0167] Examples 1-6 are implementation examples, and Examples 7-8 are comparative examples.
[0168] [Example 1]
[0169] 1 mL of α-alumina (product name "α-alumina, average particle size 0.5 μm", manufactured by Fujifilm and Koichi Chemical Co., Ltd.) was weighed as a catalyst. The catalyst was packed into a stainless steel (SUS304) reaction tube with an inner diameter of 1.02 cm and a length of 30 cm and placed inside a tubular electric furnace. While passing nitrogen gas through the tube, the catalyst packing section was heated to 475°C to dehydrate the catalyst. Then, a nitrogen / HFC-134a 0.1 / 1 (mol / mol) gas mixture was passed through for a contact time of 4.7 seconds to carry out the HF removal reaction to generate HFO-1123.
[0170] In addition, the concentration of water in a 0.1 / 1 (mol / mol) mixture of nitrogen / HFC-134a was determined using a Karl Fischer moisture analyzer, and the result was 5 ppm by mass.
[0171] [Example 2~Example 8]
[0172] In Examples 2 through 8, except that the catalyst was changed and the various conditions were changed to the values recorded in Table 2, the HF removal reaction was carried out in the same manner as in Example 1.
[0173] The catalysts used in Examples 2 through 8 will be described below.
[0174] (Example 2)
[0175] Alpha-alumina (product name "SA52124", manufactured by Saint-Gobain) was used as the catalyst.
[0176] (Example 3)
[0177] Alpha-alumina (product name "SA52238", manufactured by Saint-Gobain) was used as the catalyst.
[0178] (Example 4)
[0179] α-alumina (product name "FGL-40", manufactured by Iwatani Chemical Industry Co., Ltd.) was used as the catalyst.
[0180] (Example 5)
[0181] Alpha-alumina (product name "LT303D", manufactured by Nippon Light Metals Co., Ltd.) was used as the catalyst.
[0182] (Example 6)
[0183] Alpha-alumina (product name "C500", manufactured by Nippon Light Metals Co., Ltd.) was used as the catalyst.
[0184] (Example 7)
[0185] γ-alumina (product name "N612N", manufactured by Nippon Chemical Co., Ltd.) was used as the catalyst.
[0186] (Example 8)
[0187] The catalyst used is primarily composed of θ-alumina and partially of α-alumina (product name "SA3177", manufactured by Saint-Gobain).
[0188] The Lewis acid sites of each catalyst were determined using the "BELCAT II" instrument manufactured by MicrotracBEL and by NH3-TPD. The determination conditions were as described above. The Lewis acid sites were determined before the catalysts were loaded into the reaction tubes.
[0189] For the catalyst in Example 6, XRD measurements were performed using a SmartLab X-ray diffraction apparatus manufactured by Rigaku Corporation. The resulting diffraction pattern is shown below. Figure 1 .exist Figure 1 The diffraction pattern shows peaks at 2θ = 26.62, 35.21, 37.85, 43.43, 52.65 and 57.61 Å, confirming the presence of α-alumina.
[0190] Furthermore, peaks were observed at 2θ = 31.51, 32.78, 36.74, 38.87, 44.86, and 67.40 Å, confirming the presence of θ-alumina.
[0191] Then, Rietveld analysis was performed on the diffraction peaks of each crystal phase observed above, and the results confirmed that the content of α-alumina in the catalyst was 65.2% by mass and the content of θ-alumina was 34.8% by mass.
[0192] Similarly, the content of α-alumina was determined by XRD for the catalysts of Examples 1-5 and 7-8.
[0193] The contact time (in seconds) is calculated using the following formula.
[0194] Contact time (seconds) = [Length of catalyst packed in the reactor (cm)] / [Linear velocity (cm / second)]
[0195] Linear velocity refers to the rate at which fluorocarbons pass through a catalyst per unit time.
[0196] The contact time (g·second / mL) is calculated using the following formula.
[0197] Contact time (g·second / mL) = [catalyst loading amount (g)] / [fluorocarbon flow rate (mL / second)]
[0198] In the reactions of Examples 1 to 8, the generated gases (hereinafter referred to as "reactor outlet gases") extracted from the reactor outlet were analyzed by gas chromatography 10 hours and 50 hours after the start of the reaction. Specifically, a chromatographic column (product name "DB-1301", manufactured by Agilent Technologies, 60 m in length, 0.25 mm in inner diameter, and 1 μm in film thickness) was mounted on a gas chromatograph (product name "GC6850", manufactured by Agilent Technologies) for analysis. The conversion of HFC-134a and the selectivity of HFO-1123 were calculated using the molar amount calculated from the area ratio (GCArea%) of the reactor outlet gas.
[0199] (HFC-134a conversion rate)
[0200] This represents the total molar amount M1 of the components other than HFC-134a in the reactor outlet gas relative to the molar amount M of HFC-134a supplied to the reactor. 134a The ratio (mol%).
[0201] HFC-134a conversion rate (%) = (M1 / M 134a )×100
[0202] (Selectivity of HFO-1123)
[0203] M represents the molar amount of HFO-1123 contained in the gas exiting the reactor. 1123 The ratio (mol%) of the total molar amount M1 of compounds other than HFC-134a contained in the reactor outlet gas.
[0204] HFO-1123 selection rate (%) = (M 1123 / M1)×100
[0205] [Table 2]
[0206]
[0207] As shown in Table 2, in Examples 1 to 6, since the process of producing the fluoroolefin shown in Formula (2) by contacting the fluorocarbon compound shown in Formula (1) with the catalyst is included, the catalyst contains more than 65% by mass of α-alumina, and the amount of Lewis acid sites determined by the ammonia temperature-programmed desorption method is 0.005 to 0.10 mmol / g, the conversion rate is higher than before, and the decrease in conversion rate during long-term manufacturing is suppressed.
[0208] On the other hand, in Example 7, which did not contain α-alumina and had a Lewis acid site concentration greater than 0.10 mmol / g, the conversion rate was very low compared to Examples 1-6.
[0209] Furthermore, in Example 8, which contained α-alumina but had Lewis acid sites in amounts greater than 0.10 mmol / g, the conversion rate was at the same level after 10 hours compared to Examples 1–6, but the conversion rate decreased significantly during manufacturing at 50 hours and longer durations.
[0210] Furthermore, as shown in the results of Examples 1 to 6, since the process of manufacturing the fluoroolefin shown in Formula (2) by contacting the fluorocarbon compound shown in Formula (1) with the catalyst is included, and the conversion rate after 10 hours of contacting the fluorocarbon compound with the catalyst is 7 to 13%, the decrease in conversion rate during long-term manufacturing is suppressed.
[0211] [Examples 9, 10]
[0212] Furthermore, for the catalysts used in Examples 4 and 5, except that the various conditions were changed to the values recorded in Table 3, the HF removal reaction was carried out in the same manner as in Example 1, i.e., Examples 9 and 10. Then, the conversion rate of HFC-134a and the selectivity of HFO-1123 were calculated 10 hours and 100 hours after the start of the reaction.
[0213] [Table 3]
[0214]
[0215] As shown in Table 3, in Example 9, where the amount of Lewis acid sites was in the range of 0.008 to 0.05 mmol / g, the decrease in conversion rate during manufacturing for longer periods such as 100 hours was effectively suppressed compared to Example 10, which was outside this range.
[0216] In addition, the raw material supply rate in this embodiment is 1257 kg / hr / m 3 The raw material supply is 307 kg / h / m compared to Non-Patent Literature 1. 3 The conversion rate is about 4 times higher, which is a condition for a decrease in conversion rate. However, even with such an increase in the amount of raw materials, if the process of producing the fluoroolefin shown in formula (2) by contacting the fluorocarbon compound shown in formula (1) with the catalyst is included, and the catalyst contains more than 65% by mass of α-alumina and the amount of Lewis acid sites determined by the ammonia temperature-programmed desorption method is 0.005 to 0.10 mmol / g, the conversion rate is excellent and the decrease in conversion rate during long-term manufacturing is suppressed.
[0217] Furthermore, the full disclosure of Japanese Patent Application No. 2023-072720 is incorporated herein by reference. All documents, patent applications, and technical standards described in this specification are incorporated by reference to the extent that each document, patent application, and technical standard is specifically and separately described by reference.
Claims
1. A method for manufacturing a fluoroolefin, comprising a step of contacting a fluorocarbon compound of formula (1) with a catalyst to manufacture a fluoroolefin of formula (2). The catalyst contains more than 65% by mass of α-alumina, and the amount of Lewis acid sites, as determined by ammonia temperature-programmed desorption, is 0.005–0.10 mmol / g. CX 1 X 2 F-CX 3 X 4 H …(1) CX 1 X 2 =CX 3 X 4 …(2) In equations (1) and (2), X 1 X 2 X 3 and X 4 Each can be used independently to represent a hydrogen atom or a fluorine atom, where, X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
2. The method for manufacturing fluoroolefins as described in claim 1, wherein, The amount of the Lewis acid site is 0.005–0.05 mmol / g.
3. The method for manufacturing fluoroolefins as described in claim 1, wherein, The amount of the Lewis acid site is 0.008–0.05 mmol / g.
4. The method for manufacturing fluoroolefins as described in claim 1, wherein, The amount of the fluorocarbon compound supplied to the catalyst is 350 kg / hr / m³. 3 above.
5. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluorocarbon compound is at least one selected from 1,1,1-trifluoroethane, 1,1,2-trifluoroethane, 1,1,2,2-tetrafluoroethane, and 1,1,1,2-tetrafluoroethane.
6. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluoroolefin is at least one selected from 1,2-difluoroethylene, 1,1-difluoroethylene, and trifluoroethylene.
7. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluorocarbon compound is 1,1,1,2-tetrafluoroethane, and the fluoroolefin is trifluoroethylene.
8. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluorocarbon compound is brought into contact with the catalyst at a temperature of 300–800°C.
9. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluorocarbon compound is brought into contact with the catalyst in the presence of an inert gas. The inert gas is selected from at least one of nitrogen, helium, argon, octafluorocyclobutane, and carbon dioxide.
10. The method for producing fluoroolefins as claimed in claim 1 or 4, further comprising the step of drying the catalyst before contacting the fluorocarbon compound with the catalyst.
11. The method for manufacturing fluoroolefins as described in claim 1 or 4, wherein, The fluorocarbon compound is brought into contact with the catalyst in the gas phase in the presence of water. The concentration of the water is less than 500 ppm by mass relative to the total amount of the feed gas containing the fluorocarbon compound.
12. A method for producing a fluoroolefin, comprising a step of contacting a fluorocarbon compound of formula (1) with a catalyst to produce a fluoroolefin of formula (2). The conversion rate of the fluorocarbon compound after contacting the catalyst for 10 hours is 7.0-13.0%, and the conversion rate after 50 hours, relative to the conversion rate after 10 hours (i.e., the conversion rate retention rate), is above 69%. CX 1 X 2 F-CX 3 X 4 H …(1) CX 1 X 2 =CX 3 X 4 …(2) In equations (1) and (2), X 1 X 2 X 3 and X 4 Each can be used independently to represent a hydrogen atom or a fluorine atom, where, X 1 X 2 X 3 and X 4 At least one of them is a fluorine atom.
Citation Information
Patent Citations
Manufacturing method of fluoroolefin
JP2019196347A
Conference server and conference server control method
JP2023072720A